2014
DOI: 10.1080/21501203.2014.963720
|View full text |Cite
|
Sign up to set email alerts
|

Hymenoscyphus fraxineusvs.Hymenoscyphus albidus– A comparative light microscopic study on the causal agent of European ash dieback and related foliicolous, stroma-forming species

Abstract: Five species of Hymenoscyphus that fruit on black stromatized parts of dead leaves of deciduous trees are presented, giving details on their morphological and ecological characteristics. Several of these species have previously been misplaced in rutstroemiaceous genera because of the presence of a substratal stroma. However, the heteropolar, scutuloid ascospores with an often hook-like lateral protrusion at the rounded apex and the ascus apical ring of the Hymenoscyphus-type represent two reliable morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 77 publications
4
96
0
2
Order By: Relevance
“…A major concern in our results is the coexistence of H. fraxineus and H. albidus in this forest, especially when some authors had pointed out that H. albidus appeared to be extinct in the Czech Republic [15]. H. albidus has been infrequently recorded in Europe over the last 150 years [15].…”
Section: H Fraxineus Vs H Albidusmentioning
confidence: 88%
See 2 more Smart Citations
“…A major concern in our results is the coexistence of H. fraxineus and H. albidus in this forest, especially when some authors had pointed out that H. albidus appeared to be extinct in the Czech Republic [15]. H. albidus has been infrequently recorded in Europe over the last 150 years [15].…”
Section: H Fraxineus Vs H Albidusmentioning
confidence: 88%
“…H. albidus has been infrequently recorded in Europe over the last 150 years [15]. However, lastly, several authors have reported the presence of H. albidus in forests affected by H. fraxineus.…”
Section: H Fraxineus Vs H Albidusmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research based on DNA sequences of isolates from Switzerland and other European countries revealed that H. albidus represents an aggregate of two clearly delimited species (Queloz et al 2011). One was related to the non-pathogenic H. albidus sensu stricto, which had been known in Europe since 1850 (Kowalski and Holdenrieder 2009a;Baral and Bemmann 2014). The second was described as a new cryptic species, Hymenoscyphus pseudoalbidus, with Ch.…”
Section: Introductionmentioning
confidence: 99%
“…F. rhynchophylla Hance). Also, the range of H. fraxineus may enfold only the eastern part of the ranges of its hosts, where by today this fungus has been recorded (see Figure 24 in Baral & Bemmann 2014). Conversely, in Europe the still easternmost point of occurrence of H. fraxineus was established in eastern Ukraine (Davydenko et al 2013).…”
Section: Methodsmentioning
confidence: 99%